The Amount of Breast Milk Intake and the Decrease of Total Bilirubin Level in Hyperbilirubinemia Neonates Undergoing Phototherapy - Janah, Nur; Wahyuningrum, Eka; Yulianti, Natalia Ratna (Infomasi dan Promosi Kesehatan, 2024)
Introduction: Breast milk has been proven to be able to reduce total bilirubin levels in newborns with hyperbilirubinemia. There has been a lot of research on the frequency of breastfeeding and reduced bilirubin levels, but there is still little research on the amount of breast milk intake and the reduced bilirubin levels in newborn with hyperbilirubinemia undergoing phototherapy. Purpose: This study aimed to measure the relationship between the amount of breast milk intake and the decrease in total bilirubin levels in hyperbilirubinemia newborn undergoing phototherapy. Method: The design of this study is an analytical observational approach with a cross-sectional design. The sampling technique used was total sampling with a total of 51 newborns with hyperbilirubinemia. Data were collected from medical records at a hospital in Semarang. The data were analyzed using an Unpaired t-test. Results: The results of the Unpaired t- test was p-value of 0.100 (P>0,005) Conclusion: There is no significant relationship between the amount of breastfeeding and the decrease in total bilirubin levels in newborns with hyperbilirubinemia undergoing phototherapy.